Successful Treatment of Refractory Inspissated Bile Syndrome Using Gastrografin - Justin J. Guan; Mohammad A. Amarneh (Journal of Clinical Interventional Radiology ISVIR)
Inspissated bile syndrome (IBS) is a rare cause of obstructive jaundice in infants. Despite drainage and irrigation, obstruction may persist in some cases with limited further options. This report presents a case of persistent IBS in a 5-month-old female with worsening liver failure despite cholecystostomy and saline irrigation, and a last-ditch effort was made to irrigate with Gastrografin. Patient's bilirubin decreased from 15.5 to 8.3 mg/dL after 1 day. Her bilirubin and liver functions tests normalized by 2 weeks. Gastrografin's hyperosmolarity promotes intraluminal fluid shift and stimulates smooth muscle contraction, which may explain its effectiveness in treating refractory IBS.